IMPLEMENTATION OF POLICY REGULATION OF THE MINISTER OF AGRARIAN AND SPATIAL/HEAD OF NATIONAL LANDSCAPER AGENCY NUMBER 12 OF 2017 CONCERNING ACCELERATION OF FULL SYSTEMATIC LAND REGISTRATION BY THE NATIONAL LAND AGENCY IN CIAMIS DISTRICT: Array - Harry Fajar Kurnia; Agus Dedi (JGSRD: Journal of Government Science and Rural Development, 2020)
The research began with a miscommunication when counseling regarding the implementation of the Systematic Complete Land Registration policy between the National Land Agency and the Village Government and the Village Adjudication Committee which was held in Cicapar Village, Banjarsari District, Ciamis Regency. This happens because the National Land Agency as the policy implementer does not participate in assisting in the implementation of the field, even though it is clear in the rules that the National Land Agency must be directly involved in the field and there are inconsistencies with the rules or decisions regarding levies carried out by the Village Government and the Village Adjudication Committee to the community. The purpose of this study is to order the administration of land. The method used in this research is analytical descriptive research method. Based on the research that has been obtained, the results of the Policy Implementation of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 12 of 2017 Concerning the Complete Systematic Land Registration Acceleration by the National Land Agency in Cicapar Village, Banjarsari District, Ciamis Regency are not going well. This is due to non-compliance with the National Land Agency on existing regulations and the low quality of implementing resources in the field. The obstacles of the findings of the research results are miscommunication when counseling to the community, the absence of a special office for the Village Adjudication Committee, the low quality of the resources of the Village Adjudication Committee, the majority of which only received education up to high school level, and none of the Village Adjudication Committees have experience in the land sector. Then as for the efforts made to overcome the obstacles faced by implementing coordination first before implementing the agenda or activity.